(A-LIEP 2011): Internationalization and Collaboration: The Case of the Hong Kong Library Association / Leo F.H. Ma and Venia Y.M. Mak - F.H. Ma, Leo; Y.M. Mak, Venia (2011)
The Hong Kong Library Association was established in 1958 by a few enthusiastic librarians in Hong Kong. Over its 53-year history, it has emerged into a unique library and information professional body, engaging local librarians from all sectors, while also having a global reach. This paper gives a brief overview of the history of the Association and its major developmental stages. In the past two decades, the Association has been actively advocating for the library profession both regionally and internationally. From the perspective of Greater China, the Association has been serving as a ―bridge‖ to facilitate communication between library associations in Mainland China, Taiwan and Macau. In response to the fast changing library scene in the Asia-Pacific region, this paper points out that the Association can play a more active role by collaborating more closely with regional library associations and societies. The Association can also provide more consultancy services to help professionalizing the library associations of developing countries in South East Asia. Apart from mounting international and regional conferences, the Association has attempted to collaborate with other professional bodies, such as the former IEE (HK) Management Section and the Evergreen Education Foundation, in order to foster international cross-disciplinary co-operation. This paper also highlights the increasingly diversified needs of the Association‘s membership and the major challenges encountered by the Association which - unlike many other library associations in the region - is not a publicly funded organization. This paper also discusses the possibilities of reviewing the role and structure of the Council of the Association, in order to meet these challenges in the global era.